Refractory Helicobacter pylori gastritis: The hidden predictors of resistance. (December 2019) - Hanafy, Amr Shaaban; Seleem, Waseem M.
Highlights: Failure of Helicobacter pylori eradication is documented in 20% of patients. Study of occult H. pylori persistence in gastric biopsies despite negative faecal antigen test (FAT). Even after salvage therapy, 24.5% of patients showed persistent symptoms with negative FAT. Cultures were most commonly susceptible to norfloxacin, moxifloxacin, doxycycline and amikacin. Variables correlated with H. pylori persistence are insulin resistance, macrolide exposure, fatty liver disease and HCV. Abstract: Objectives: Failure of Helicobacter pylori eradication is documented in 20% of patients. Some patients show a negative faecal antigen test (FAT) with persistent symptoms after therapy. The aim of this study was to detect occult H. pylori infection in patients with persistent symptoms despite FAT negativity following therapy. Methods: A total of 200 symptomatic patients presenting with dyspepsia and positive FAT were treated with H. pylori triple therapy for 2 weeks. Refractory patients received levofloxacin-based salvage therapy. Upper gastrointestinal endoscopy was performed for patients with persistent symptoms despite negative FAT after salvage therapy. Gastric biopsies were exposed to rapid urease test and RFLP-PCR for clarithromycin resistance in domain V of 23S rRNA (2142/2143 point mutations) as well as culture and antimicrobial susceptibility testing (AST). Results: A total of 136 patients responded to classic triple therapy with negative FAT, and 15 patients showed persistent symptoms with positive FAT and received salvage therapy. The remaining 49 patients showed persistent symptoms despite negative FAT, therefore gastric biopsies with rapid urease test were performed. Clarithromycin resistance was confirmed in 12/49 patients (24.5%). Cultures were most commonly susceptible to norfloxacin ( n  = 18), moxifloxacin ( n  = 13), doxycycline ( n  = 11) and amikacin ( n  = 8). Non-responders with negative FAT had moderate or severe fatty liver disease (26.5% and 32.7%, respectively), 40.9% had hepatitis C virus (HCV) infection, and they had significantly higher HOMA-IR and HbA1c. Conclusion: Diabetes mellitus, HCV and non-alcoholic fatty liver disease predispose to refractory H. pylori requiring culture and AST.